Hepatitis B Virus X Protein Inhibits Tumor Suppressor miR-205 through Inducing Hypermethylation of miR-205 Promoter to Enhance Carcinogenesis - Tao Zhang; Junping Zhang; Ming Cui; Fabao Liu; Xiaona You; Yumei Du; Yuen Gao; Shuai Zhang; Zhanping Lu; Lihong Ye; Xiaodong Zhang (2013)
The infection of hepatitis B virus (HBV) is closely associated with the development of hepatocellular carcinoma (HCC), in which HBV X protein (HBx) plays crucial roles. MicroRNAs are involved in diverse biologic functions and in carcinogenesis by regulating gene expression. In the present study, we aim to investigate the underlying mechanism by which HBx enhances hepatocarcinogenesis. We found that miR-205 was downregulated in 33 clinical HCC tissues in comparison with adjacent noncancerous hepatic tissues. The expression levels of miR-205 were inversely correlated with those of HBx in abovementioned tissues. Then, we demonstrated that HBx was able to suppress miR-205 expression in hepatoma and liver cells. We validated that miR-205 directly targeted HBx mRNA. Ectopic expression of miR-205 downregulated HBx, whereas depletion of endogenousmiR-205 upregulated HBx in hepatoma cells. Notably, our data revealed that HBx downregulated miR-205 through inducing hypermethylation of miR-205 promoter in the cells. In terms of function, the forced miR-205 expression remarkably inhibited the HBx-enhanced proliferation of hepatoma cells in vitro and in vivo, suggesting that miR-205 is a potential tumor-suppressive gene in HCC. HBx-transgenic mice showed that miR-205 was downregulated in the liver. Importantly, HBx was able to abrogate the effect of miR-205 on tumor suppression in carcinogenesis. Therefore, we conclude that HBx is able to inhibit tumor suppressor miR-205 to enhance hepatocarcinogenesis through inducing hypermethylation of miR-205 promoter during their interaction. Therapeutically, miR-205 may be useful in the treatment of HCC.